(3TaGA GdBdGe aj WH Cgd GdESdGes - (3jhSa Hf eMeO Hf eSYhO Hf eMeO GdYHGOj (B- (3HGdJNaja (B- (3Ke GdYbjdj, CHh GdeXaQ, LeGd GdOjf GdoqSnqQnepqQj,J (B776 (3g` s
(3ChdgG (B:s
(3hHYO , aEf MaX GdfaS ef Cge GdhGLHGJ ` heQGYGJ UMI GdCHOGf ef s
(3BNQgG (B:s
(3hEfeG QRb GdYGajI ai GdOfjG hGdYah ai GdCNQI abO MUd dg NjQ GdOGQjf s
(3bSeg Edi KdGKI CLRGAs
(3cJHgG CMO JdGejP GdeDda ai MjGJgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B250 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B332s
Keywords: (3GdWHs